SISTEM INFORMASI MANAJEMEN TAMAN KANAK-KANAK (STUDI KASUS : TAMAN KANAK-KANAK (TK) MEKAR SARI DESA AMBAWANG) - Meliana; Veri Julianto; Khairul Anwar Hafizd (Aisyah Journal Of Informatics and Electrical Engineering, 2020)
Current technological developments can be done to facilitate work. One of them can be applied to support management information system that focus on management TK Mekar Sari. The problems that exist in the process of acceptance of new students are still conventional (manual) and the class division process is still shared conventionally (manually) using Microsoft Excel. So it can take much time for class and student division in each semester. Based on the problem, the system is called "Kindergarten Management Information System (case study: Kindergarten (TK) Mekar Sari village Ambawang)". The system is built using the PHP programming language with a native framework. While the database development uses MySQL that works for the database server. Design of the display interface that author builds are created using Adobe XD CC 2019. As well as the draft database using Entity Relationship Diagram, Data Flow Diagram and Flowchart. This system can facilitate admins, principals and prospective registrants in the registration process, class division and Administration data collection to make it easier, faster and efficient both in terms of time, place, cost and energy at kindergarten (TK) Mekar Sari in Ambawang village.